(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the early stages of studying proverbs in the history of linguistics, their scientific classification, and the formation of research methodology. The study of proverbs is viewed as a complex linguocultural process that emerged at the intersection of several disciplines such as folklore studies, ethnolinguistics, semasiology, and paremiology. Proverbs are analyzed as linguistic expressions of folk wisdom, focusing on their semantic, morphological, and pragmatic structures, as well as the genesis of proverbs found in ancient written monuments. The article provides a comparative analysis of early research in Eastern and Western linguistic traditions and examines the views of scholars such as Mahmud al-Kashgari, Aristotle, Erasmus of Rotterdam, V. Dal, and G. Permyakov as historical sources for the study of proverbs. Theoretical foundations for the study of proverbs as stable linguistic units are discussed, along with approaches that uncover their lexical and semantic nature and issues related to the emergence of paremiology as an independent scientific discipline.